Pendampingan Ketrampilan Wirausaha Pembuatan Makanan Ringan Bagi Anak - Anak Yatim Lksa Al-Amin Desa Kedungturi Kecamatan Taman Sidoarjo - Sutono Sutono; Ach Kusnan Arif (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Community service is an urgent matter for the head of the Al-Amin Orphanage Children's Social Institution to assist orphaned children through assistance in increasing creative skills through making snacks. This aims to enable them to be creative and the results can become selling points if developed intensively. The assisted subjects were 20 poor elementary school age children. The activity time is from 01 September 2022 – 31 December 2022 every 15.30-17.00. The place of implementation is at the Al Amin Orphanage Children's Social Institution, Kedungturi Taman Sidoarjo. The result of the implementation of activities in this assistance is the development of the skills of orphaned children through assistance with techniques for making snacks. The steps taken were to form six groups to work together to express their ideas and imagination into a work. Each group is required to present their work and other groups evaluate their friends' work. With each result, the children are then trained to sell snacks resulting from their mentoring, so that every time there is an important event in Kedungturi village they always set up a sales stand to sell the snacks they made based on their mentoring experience over the past 4 months.